Action Research Methodology in Educational Research: A Critical Review of the Evolution of Concepts, Models, Implementation, and Contemporary Challenges - Soni Sultansah; Yohanna Zuriyah; Nur Sholehah; Bayu Bambang Nurfauji; Tedi Priatna (Penerbit Hellow Pustaka, 2026)
Action Research is a research methodology oriented toward improving practice through cycles of planning, action, observation, and reflection. This article aims to critically analyze the conceptual evolution, model development, implementation, and contemporary challenges of Action Research within educational research. The study employs a Critical Literature Review (CLR) approach, analyzing relevant scholarly literature through processes of identification, selection, evaluation, and thematic synthesis. The findings indicate that Action Research has evolved from a practical problem-solving approach into a methodology that is reflective, collaborative, and focused on developing evidence-based educational practices. Its implementation contributes to enhancing the quality of learning, teacher professionalism, and educational innovation. However, its application still faces various challenges, including limited methodological competence, difficulties in conducting literature reviews and identifying research gaps, heavy administrative burdens, and pressures regarding scholarly publication and adaptation to digital technology. Therefore, strengthening research competence, fostering a culture of reflection and professional collaboration, and utilizing technology ethically are crucial factors in improving the quality of Action Research implementation. This article is intended to serve as a conceptual reference for researchers, academics, and educational practitioners in developing action research that is more systematic, innovative, and relevant to the dynamics of education.